Inactivated Rothia nasimurium promotes a persistent antiviral immune status in porcine alveolar macrophages - Tort-Miró, Aida; Alonso, Uxía; Martín-Mur, Beatriz; Muñoz-Basagoiti, Jordana; Zeng, Yan; Marín-Moraleda, David; Ezcurra, Enrique; Montaner-Tarbes, Sergio; Navas, María J.; Muñoz, Marta; Monleón, Paula; González-Oliver, Judith; et al. (Frontiers in Immunology, 2025)
Globalization has increased the incidence of infectious diseases in livestock, further aggravated by the reduction of antibiotic usage. To minimize the resulting economic consequences to the meat production industry, as well as the risk of zoonotic events, the use of immunostimulants has emerged as a potential strategy to enhance animal resilience to diseases. In particular, the capability of bacterial-based immunostimulants to modulate innate immune cells functionality makes them cost-effective candidates as vaccine adjuvants, antimicrobials, or preventive immunostimulators inducing long-term innate immune memory in livestock. However, further research is required to identify novel bacterial strains with immunostimulatory properties. Here we characterized in vitro the immunostimulatory properties of Rothia nasimurium isolated from warthog fecal microbiota. Stimulation with heat-inactivated Rothia induced cytokine production by porcine immune cells, and a robust innate immune transcriptomic signature in porcine alveolar macrophages. Interestingly, the bacteria induced inflammasome activation and IL-1β production, thus confirming its pro-inflammatory properties, and suggesting its potential as vaccine adjuvant. Importantly, this immunostimulatory status functionally resulted in an antimicrobial state, enhancing the phagocytic capability of alveolar macrophages, and hampering the replication levels of two major porcine viral pathogens: the porcine reproductive and respiratory syndrome virus (PRRSV) and the African swine fever virus (ASFV). Moreover, macrophages showed an enhanced cytokine response upon ASFV infection several days after heat-inactivated Rothia stimulation, suggesting the induction of an innate immune memory phenotype. This nonspecific response resulted in a significant reduction of ASFV replication kinetics, demonstrating the capacity of the bacteria to induce a more resistant state in macrophages against a virus infection. Altogether, these results demonstrate the immunostimulatory capability of heat-inactivated R. nasimurium in porcine macrophages, showing potential to enhance animal resilience to diseases through the modulation of innate immune cells responsiveness to infections.